DAMPAK PENGALAMAN POLA ASUH PERMISIF TERHADAP PENERAPAN POLA ASUH ANAK USIA 0-5 TAHUN KELOMPOK PKH DI WILAYAH KERJA PUSKESMAS PASIR PANJANG, KELURAHAN PASIR PANJANG - Jane Leo Mangi; Agustina Ina; Oklan Liu Nokas; Dominggos Gonsalves; Yustinus Rindu (Jurnal Cakrawala Ilmiah, 2024)
Background: People with a weak economy tend to apply poor parenting. PKH families are recipients of social assistance registered in the Integrated Social Welfare Data (DTKS). This assistance is given to poor and vulnerable poor families with requirements. Objectives: This study aims to determine the effect of peemissive parenting experience on the application of parenting to children aged 0-5 years of the PKH group in the Pasir Panjang Village area. Methods: This type of research is analytic with a cross sectional design... Sample: the sample in this study was obtained using purposive sampling technique totaling 52 respondents. Data collection was carried out using a questionnaire filled out by respondents. Results: The results of multiple logistic regression statistical tests, there is no significant influence between the experience of permissive parenting of mothers with the application of authoritarian parenting as evidenced by p value 0.240, there is no significant relationship between the experience of permissive parenting with the application of permissive and democratic parenting, with p value 0.883 and 0.107.